PERAN GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MATA PELAJARAN PAI - Achadah, Alif; Mulyati, Eka Desi (Universitas Islam Sultan Agung, 2020)
Education is very important in the development of a nation. With education the nation can become more advanced with the presence of a younger generation who is able to answer the challenges of the times. But in education it is not only aimed at increasing one's knowledge, but education also aims to make someone's behavior and morals better. So that in the application of learning in schools, the role of Islamic Education teachers is very important in to increase student motivation. In this study, taking the problem of